Penerapan Model Pembelajaran Kolaboratif dengan Teknik Think Aloud Pair Problem Solving pada Materi Hidrokarbon Siswa Kelas X SMA Negeri 6 Palu - Durufin, Ekanovi Pratiwi A.; Sabang, Sri Mulyani; Said, Irwan (Jurnal Akademika Kimia, 2018)
This study was conducted to determine differences of the student’s learning outcomes that was applied by collaborative learning model with technique think aloud pair problem solving (TAPPS) and was applied by lecture method in the hydrocarbon material against the student’s learning outcomes in class X SMAN 6 Palu. The collaborative learning model was think aloud pair problem solving technique on the hydrocarbon material class X SMAN 6 Palu. The type of research was a quasi-experimental with research design pretest posttest control group design. Population in this research was whole students in class X SMAN 6 Palu, academic year 2015-2016 consisting of six classes totaling 115. The sampling technique used was a purposive sampling. The samples in this research was an experiment class with 17 students and a control class with 8 students. Data analysis techniques used was non-parametric and statistical method of Mann-Whitney U-test. Research result showed the output Rank for mean score of the experiment class was bigger than the control class 22.41 ˃ 13.83. The output statistics test, Sig. 2-tailed (0.13) 0.05 ˂ and Ucalculation (78) ˂ Utable (93). From the findings of hypothesis testing, H0 was rejected and Ha was accepted then it can be concluded that there were significant differences learning outcomes in the student’s with the collaborative learning model technique think aloud pair problem solving (TAPPS) with the lecture method on the hydrocarbon material against the learning outcome of students in class X SMAN 6 Palu.